Transcranial Alternating Current Stimulation Attenuates Visual Motion Adaptation - Kar, Kohitij (Society for Neuroscience, 2014)
Transcranial alternating current stimulation (tACS) is used in clinical applications and basic neuroscience research. Although its behavioral effects are evident from prior reports, current understanding of the mechanisms that underlie these effects is limited. We used motion perception, a percept with relatively well known properties and underlying neural mechanisms to investigate tACS mechanisms. Healthy human volunteers showed a surprising improvement in motion sensitivity when visual stimuli were paired with 10 Hz tACS. In addition, tACS reduced the motion-after effect, and this reduction was correlated with the improvement in motion sensitivity. Electrical stimulation had no consistent effect when applied before presenting a visual stimulus or during recovery from motion adaptation. Together, these findings suggest that perceptual effects of tACS result from an attenuation of adaptation. Important consequences for the practical use of tACS follow from our work. First, because this mechanism interferes only with adaptation, this suggests that tACS can be targeted at subsets of neurons (by adapting them), even when the applied currents spread widely throughout the brain. Second, by interfering with adaptation, this mechanism provides a means by which electrical stimulation can generate behavioral effects that outlast the stimulation.